2008
DOI: 10.1158/1541-7786.mcr-08-0189
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Profiling Unveils S100A8/A9 as Candidate Markers in H-Ras-Mediated Human Breast Epithelial Cell Invasion

Abstract: The goal of the present study is to unveil the gene expression profile specific to the biological processes of human breast epithelial cell invasion and migration using an MCF10A model genetically engineered to constitutively activate the H-ras or N-ras signaling pathway. We previously showed that H-Ras, but not N-Ras, induces MCF10A cell invasion/migration, whereas both H-Ras and N-Ras induce cell proliferation and phenotypic transformation. Thus, these cell lines provide an experimental system to separate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 31 publications
6
68
0
1
Order By: Relevance
“…Our previous studies identified S100A8 and S100A9 as candidate markers for cell invasion in breast epithelial cells (33) and showed that these proteins up-regulated MMP-2, causing invasive phenotype in SNU-484 cells (25). The results obtained from this study demonstrated a dose-dependent down-regulation of S100A8 by denbinobin in SNU-484 cells, suggesting the involvement of S100A8 in the denbinobininduced invasive phenotype.…”
Section: Discussionsupporting
confidence: 61%
“…Our previous studies identified S100A8 and S100A9 as candidate markers for cell invasion in breast epithelial cells (33) and showed that these proteins up-regulated MMP-2, causing invasive phenotype in SNU-484 cells (25). The results obtained from this study demonstrated a dose-dependent down-regulation of S100A8 by denbinobin in SNU-484 cells, suggesting the involvement of S100A8 in the denbinobininduced invasive phenotype.…”
Section: Discussionsupporting
confidence: 61%
“…Enzymatic degradation of the extracellular matrix is a crucial step in cancer invasion and metastasis. Another previous study supports the hypothesis that S100A8 is more closely associated with MMP9 expression mediated by the extracellular-signal-regulated kinase pathway, whilst S100A9 has a major role in MMP2 upregulation that is dependent on p38 mitogen-activated protein kinase (MAPK) signaling (23). A further study reported that S100A8 and S100A9 contribute to colorectal carcinoma cell survival and migration via the Wnt/β-catenin pathway.…”
Section: Discussionsupporting
confidence: 60%
“…Although S100A8/A9 protein has been shown to exert apoptotic effect against various tumor cells including colon carcinoma cells (Ghavami et al, 2004) and breast cancer cells and neuroblastoma cells (Ghavami et al, 2008a), the effect of S100A8/ A9 on cell viability has been reported to be dependent on concentration exposed. S100A8/A9 resulted in significantly reduced cell viability at concentration above 50 μg/ml, while it at concentration lower than 25 μg/ml promotes proliferation and migration of various cancer cells (Ghavami et al, 2008b;Hermani et al, 2006;Moon et al, 2008). We observed that S100A8/ A9 at high concentration (30 μg/ml) exerts apoptotic effects in gastric cancer cells (Fig.…”
Section: A B Cmentioning
confidence: 63%